Bioethics and law: the importance of promoting training in legal bioethics - Bavio, Paula Siverino (2021)
Bioethics is defined in the first edition of the Encyclopedia of Bioethics edited by Warren Reich (1978) as "the systematic study of human behavior in the area of life sciences and health care, while such conduct is examined in the light of moral principles and values. "Then, in the 1995 edition will be definid as "... the systematic study of decisions moral-including visions, behaviors decisions and moral-political science of life and health care, using a variety of ethical methodologies in ethical context. The moral dimensions discussed in bioethics are constantly evolving, but tend to focus on some major questions: What is or should be the moral vision of one (or society)? What kind of person should be one (or should be society)? What should be done in specific situations? How we harmoniously? Interdisciplinary Bioethics vocation has led to a fertile field of study in various scientific and social areas, linked by the interest in reflection on the present and future of humanity. Formally born in the seventies in the context of concern for the ethical regulation of research on human beings, today, at least in Europe and Latin America, is considered an essential discipline for human survival while dealing with the relations between ethics, technology, society, equality and development, considering that not everything that is technically possible is ethically recommended.